PERAN MODERASI FRAMING DAN GAYA KOGNITIF TERHADAP BIAS EFEK URUTAN BUKTI DALAM KEPUTUSAN PENGANGGARAN - Wulandari Fitri Ekasari; Supriyadi Supriyadi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2016)
This study is aimed to empirically test the moderating roles of information framing and cognitive style on recency effect in budgeting decision, as a part of management accounting decisions. Laboratory experimental method used in this study with a 2x2x2 between-subjects design involving participants of 100 undergraduate accounting students at two universities in Central of Java and Yogyakarta provinces. The results of this study indicate that in the Step-by-Step (sequentially) response mode, the occurence of recency effects can be mitigated by information framing. In contrast, participants in the End-of-Sequence (simultaneously) response mode did not experience any order effects. Moreover, the interesting finding is that the interaction effect between information order and response modes indicating that the End-of-Sequence response mode alone can reduce the recency effects. However, the prediction of interaction effect between information order, information framing, and cognitive styles in both Step-by-Step and End-of-Sequence was not supported.